Silence as possibility in postwar everyday life - Eastmond, Marita (International journal of transitional justice, 2012)
Silence is a form of communication as multifaceted as speech and as such conveys a broad range of contextually situated social meanings. Often silence is understood as a form of denial and inherently detrimental to processes of reconciliation, but it may help create a sense of ‘normality’ and facilitate encounters between former foes. This article enquires into the role and meanings of silence as tacit forms of communication in postwar social processes and everyday life among people of different ethnic groups in Bosnia and Herzegovina, particularly as used by the displaced and returnees. It argues that in these contentious settings, everyday social interaction employs silence in ways that empower by communicating respect and even trust, thus forming and sustaining relations important to viable local life. Silence can be used to affirm family continuity and protect close relationships. Silent claims may also ‘speak’ from a marginalized position in relation to hegemonic narratives and make moral claims. Silence may thus be understood as a pragmatic and at times successful strategy for coexistence even when reflecting continued division in the larger society.